Rancang Bangun Deteksi Kebakaran dengan Smoke Detector Addressable Berbasis Outseal PLC Mega V.3 Standart - Yuka Pakarti; Ibrahim ,; Reni Rahmadewi (Peneliti.net, 2023)
The Design and Construction of Fire Detection with Addressable Smoke Detector based on Outseal PLC Mega V.3 Standard is a fire detection system that utilizes Addressable Smoke Detector technology and Outseal PLC Mega V.3 Standard. This system is designed to detect fires early and provide timely alarms to reduce the risk of fire damage. The system consists of several main components such as Addressable Smoke Detector, Outseal PLC Mega V.3 Standard, and a sound alarm. The Addressable Smoke Detector is used to detect the presence of smoke or gases associated with fire. The Outseal PLC Mega V.3 Standard functions as the system's brain, collecting data from the Addressable Smoke Detector and making decisions to sound the alarm if a fire is detected. In the conducted testing, this system was able to accurately detect fires and provide a quick response with a sound alarm. Overall, the Design and Construction of Fire Detection with Addressable Smoke Detector based on Outseal PLC Mega V.3 Standard is a reliable and effective fire detection system to maintain safety and security in various types of buildings.